Preparation and analysis of pyroligneous liquor, charcoal and gas from lacquer wood by carbonization method based on a biorefinery process. (15th January 2022) - Hu, Sheng-Chun; Cheng, Jie; Wang, Wu-Ping; Zhu, Ya-Hong; Kang, Kang; Zhu, Ming-Qiang; Huang, Xiao-Hua
Abstract: A biomass pyrolysis polygeneration process, which comprehensively utilizes the pyrolysis products to maximize economic and environmental benefits, refers to the thermochemical conversion of biomass. The pyrolysis of lacquer wood at 300–550 °C with an increment of 50 °C was conducted in this study. Results showed that the yield of charcoal rapidly decreased from 37.94 to 26.39%, and the specific surface area (SBET ) of charcoals changed from 2.38 to 214.04 m 2 /g with the temperature increasing from 300 to 550 °C. The specific surface area of the optimal charcoal reached the maximum value (229.43 m 2 /g) at 500 °C. It was also found that the main compounds of the pyroligneous acids (PA) were phenols, ketones, alkyls, acids, and alcohols, respectively. The phenol and derivatives accounted for almost half of the total content. Besides, the PA collected from 400 °C showed the strongest antimicrobial activity against brown rot fungi (43 mm), which mainly ascribed to the highest content of ketones. Furthermore, the calorific value of the gas was reached the maximum (10.16 MJ/m 3 ) at 550 °C. With comprehensiveness, the efficient method used in this research possess good feasibility to produce charcoal, pyroligneous liquor, and gas, which is beneficial for high-valued of lacquer wood. Graphical abstract: Image 1 Highlights: The lacquer wood was subjected to an integrated polygeneration process. The charcoal, pyroligneous liquor and gas were obtained from the process. The structural characteristics of the charcoal were systemically elucidated. Pyroligneous liquor showed high inhibitory effect on bacteria and fungus. The CO and CH4 content exhibited an increasing trend as the temperature rise.